Everolimus therapy for progressive adrenocortical cancer. - Fraenkel, M; Gueorguiev, M; Barak, D; Salmon, A; Grossman, AB; Gross, D (2013)
Patients with advanced adrenocortical carcinoma (ACC) have limited treatment options after failure of chemotherapy. Tumor IGF2 expression has been shown to be amplified in the majority of cases of ACC and autocrine/paracrine activation of the IGF receptor (IGF-R) is thought to play a major role in the pathogenesis of ACC. It has been shown in vitro that inhibition of the IGF-R inhibits ACC cell proliferation. mTOR is a downstream effector of the IGFR signaling pathway; therefore, the rapamycin analog everolimus could prove to be useful for treatment of patients with ACC. Four women with ACC (ages 25-60 years) developed stage IV disease after surgery. All had progressive disease (PD) despite treatment with mitotane and other treatment modalities (etoposide, doxorubicin, cis-platinum in 3/4 patients, further streptozotocin + 5-FU in 1/4 patients, further thalidomide therapy in 2/4 patients; 1 patient progressed on an IGF-R antagonist). The patients were started on everolimus 10 mg/day orally and 2/4 patients also continued mitotane. Disease progression was monitored monthly by CT in 3/4 and after 3 months in 1/4. In all patients everolimus was well tolerated. In the three patients monitored monthly, PD was evident after 1, 3, and 4 months; in the patient evaluated after 3 months PD was also evident. In this small exploratory study, no clinically meaningful response was observed with everolimus in four patients with advanced ACC. The failure of efficacy could be related to an interaction with mitotane, multiple signaling pathways, and/or other downstream IGF-R effectors operative in the pathogenesis of ACC.